Of Time and the City: The Doyles and London Print Culture. (November 2021) - Cranfield, Jonathan
Abstract : This article examines Arthur Conan Doyle's status as a 'London' writer. It places his own experiences of the city within the same historical frame as that of his father, his uncles, and his grandfather. The Doyles had spent decades working in London print culture before Conan Doyle had even been born, and it is helpful to understand his early struggles to make his name as part of this longer literary-historical narrative. The London Doyles were able to establish their names as artists, illustrators, and writers before the tectonic plates of printing technology and public taste shifted beneath them. The article also focuses on the Doyles' status as a family of immigrant Irish Catholics who found that their faith, as well as their politics, made them perpetual outsiders.